2023
DOI: 10.1126/sciadv.add5163
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide riboside improves muscle mitochondrial biogenesis, satellite cell differentiation, and gut microbiota in a twin study

Abstract: Nicotinamide adenine dinucleotide (NAD + ) precursor nicotinamide riboside (NR) has emerged as a promising compound to improve obesity-associated mitochondrial dysfunction and metabolic syndrome in mice. However, most short-term clinical trials conducted so far have not reported positive outcomes. Therefore, we aimed to determine whether long-term NR supplementation boosts mitochondrial biogenesis and metabolic health in humans. Twenty body mass index (BMI)–discordant monozygotic twin p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 64 publications
2
24
1
Order By: Relevance
“…In a placebo-controlled, randomized, double-blind, crossover trial of older men, supplementation with NR for 21 days resulted in the activation of antiinflammatory transcriptomic signatures and decreased circulating levels of proinflammatory mediators, including IL-6, TNF, IL-2, and IL-5 (53). Multiple complementary studies and clinical trials in humans have also demonstrated the capacity of NAD + boosters to increase NAD + levels to promote beneficial effects in different contexts (53,(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…In a placebo-controlled, randomized, double-blind, crossover trial of older men, supplementation with NR for 21 days resulted in the activation of antiinflammatory transcriptomic signatures and decreased circulating levels of proinflammatory mediators, including IL-6, TNF, IL-2, and IL-5 (53). Multiple complementary studies and clinical trials in humans have also demonstrated the capacity of NAD + boosters to increase NAD + levels to promote beneficial effects in different contexts (53,(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Urolithin-A is a natural postbiotic that increases muscle strength in older people by restoring youthful mitophagy (Andreux et al, 2019; Liu et al, 2022; Singh et al, 2022). Finally, NAD + precursors mitigate pathological progression in aging or genetic mitochondrial diseases by replenishing the critical metabolic cofactor NAD + (Lapatto et al, 2023; Martens et al, 2018; Pirinen et al, 2020; Yoshino et al, 2021). In contrast to these adaptive effects, activation of mtCa 2+ uptake by Oleuropein is direct and occurs minutes after cellular exposure, translating into rapid activation of PDH activity and mitochondrial respiration 2 hours after oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-diabetic drug Metformin is being clinically tested to target aging given its geroprotective effects on lifespan and healthspan that acts at least in part by triggering mitochondrial adaptations via mitohormesis (Kulkarni et al, 2020). Other clinical therapeutic molecules such as NAD+ precursors (Covarrubias et al, 2021; Lapatto et al, 2023; Martens et al, 2018; Yoshino et al, 2021) autophagy/mitophagy activators (Andreux et al, 2019; Eisenberg et al, 2016; Ryu et al, 2016) or mitochondrial complex stabilizers (Chavez et al, 2020; Karaa et al, 2018) can prevent age-related decline indirectly by targeting other hallmarks of aging that maintain mitochondrial integrity and rewire bioenergetics during aging. In contrast, there is no approved therapy to directly stimulate the core ATP-generating bioenergetic capacity of mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Two high-resolution mass spectrometry (HRMS) equipment were used for the analysis employing an untargeted metabolite profiling method developed earlier. 16,17 For human microsomal and cytosolic samples that were used for metabolite screening, a liquid chromatography connected to a heated electrospray ionization source and a quadrupole time-of-flight mass spectrometry (LC-qTOF-MS) (1290 LC and 6540 qTOF, Agilent Technologies, Santa Clara, CA, USA) was used to acquire the data using both ionization polarities, that is, positive and negative ionization (ESI+ and ESIÀ). For recombinant metabolic enzymes and samples from different species, an ultra-high-performance liquid chromatography (UHPLC, Vanquich Flex UHPLC system Thermo Fisher Scientific, Waltham, MA, USA) coupled to HRMS (Q Exactive Classic, Thermo Scientific) was utilized.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%